Production of waste-based adsorbents for the removal of pharmaceuticals from water: chemical activation and modification - Jaria, Guilaine Marques (2021)
The sustainable development of society implies the adoption of strategies related to waste management and valorization (in a circular economy perspective) and to effluent treatment (namely for the removal of pharmaceuticals from water). Being adsorption by activated carbon (AC) a well-established method for water treatment, this work focuses on the production of AC using residues, namely sludge from pulp and paper industry, for the removal of pharmaceuticals from water. This approach aims to foster an integrated solution for the two environmental issues involved in this work. Primary pulp and paper mill sludge (PS) showed a great potential to produce carbon-based adsorbents, relatively to biological sludge (BS). Through the use of PS and a production process involving chemical activation and pyrolysis, it was possible to produce AC in both powdered and granular (using a binder agent) forms, with high surface areas (SBET) (similar to those of commercial AC with the same granulometry). The produced powdered AC presented, in batch adsorption systems, adsorption capacities for the pharmaceuticals carbamazepine (CBZ), sulfamethoxazole (SMX) and paroxetine (PAR), in the same magnitude of commercial AC. However, when applied in wastewater matrix, variations in the adsorption capacity of the produced AC for the studied pharmaceutical was observed, namely in the case of SMX, which decreased, and PAR, that increased. The produced granular AC showed, in batch adsorption systems, lower adsorption capacity for the three pharmaceuticals CBZ, SMX, and PAR, than the commercial granular AC used as reference. Also, in this case, a reduction in the adsorption capacity for CBZ and SMX was observed for wastewater matrices. In fixed-bed column studies (continuous mode) the produced granular AC presented a higher breakthrough volume and adsorption capacity for CBZ for the lower flow-rate. Also, it was observed a reduction of the adsorption capacity with the increase of the complexity of the aqueous matrix (distilled water > wastewater > multicomponente solutions – with the three pharmaceuticals – in wastewater). The application of different functionalization methods to the powdered AC surface showed to be an interesting approach, evidencing an increase in the selectivity of some functionalized AC for some of the pharmaceuticals under study, despite the general reduction in their SBET. Concluding, this work demonstrates the potential of PS from pulp and paper mill industry to produce alternative AC, particularly in the powdered form, to be applied in the removal of pharmaceuticals from water.